Best answer gets 10 points, and you no doubt get a prize from the lecturer? Is that fair? :)
Anyway.
Differentiate implicitly to find the gradient:
2xb^2 + 2yy'a^2 = 0
y' = (-xb^2)/(ya^2).
Thus, the equation of the tangent at any point (a cos t, b sin t) is:
y - b sin t = y'(x - a cos t).
Now, we find the x and y intercepts:
When x = 0, we get y = b sin t- ay' cos t.
When y = 0, we get x = (-b sin t)/y' + a cos t.
Thus, the area of the triangle is 0.5(b sin t- ay' cos t)((-b sin t)/y' + a cos t).
Now, take a second to shudder, and lets dive into differentiating it.
I'm going to ignore the 0.5 on the front, it doesn't affect anything.
Expand it:
-b^2 (sin t)^2 / y' +ab sin t cos t + ab sin t cos t - a^2 y' (cos t)^2
Simplify:
2ab sin t cos t - b^2(sin t)^2 / y' - a^2 (cos t)^2 * y'.
Must be about time to substitute in for y'.
2ab sin t cos t - b^2(sin t)^2 * (b sin t * a^2)/(-a cos t * b^2) - a^2 (cos t)^2 * (-a cos t * b^2)/(b sin t * a^2).
Simplify again:
2ab sin t cos t + ab (sin t)^3/cos t + ab (cos t)^3/sin t.
Ah, how nice and symmetrical. We must be doing something right.
OK, again I'm going to ignore the constant factor of ab, since it doesn't affect anything.
2 sin t cos t + (sin t)^3/cos t + (cos t)^3/sin t
And now for the big step. Differentiate:
[2 (cos t)^2 - 2 (sin t)^2] + [(3 (sin t)^2 (cos t)^2 + (sin t)^4)/(cos t)^2] + [(-3 (cos t)^2 (sin t)^2 - (cos t)^4)/(sin t)^2].
Put everything over a common denominator of (cos t)^2(sin t)^2.
OK, this is getting to hard to type, so I'm going to let A = cos t, B = sin t :)
The numerator becomes 2A^4B^2 - 2B^4A^2 + 3B^4A^2 + B^6 - 3A^4B^2 - A^6, which we want equal to 0.
We can simplify that slightly..
B^6 + B^4A^2 - B^2A^4 - A^6.
Now, divide by A^6, and let c=B/A.
c^6 + c^4 - c^2 - 1 = 0.
c^4(c^2 + 1) - (c^2 + 1) = 0
(c^4 - 1)(c^2 + 1) = 0
c^4 = 1 or c^2 = -1
The second case is impossible, so c^4 = 1, and c = 1 or -1.
Thus we need cos t / sin t = 1 or -1, so 1/tan t = 1 or -1, so tan t = 1 or -1.
That means t = 45 degrees or -45 degrees, but we want the one in the first quadrant, so t = 45 degrees.
Finally, we go back to start again:
x = a sqrt(2)/2, y = b sqrt(2)/2.
So y' = (-xb^2)/(ya^2) = -b/a.
So the equation is
y - b sqrt(2)/2 = (-b/a)(x - a sqrt(2)/2).
Or written nicely, ay + bx = absqrt(2).
Nice to see the answer comes to something simple.. theres probably a nicer proof :(
2006-12-02 13:54:17
·
answer #1
·
answered by stephen m 4
·
2⤊
0⤋
There is a much simpler way to do this that requires minimal math but considerable insight via a simple scaling transform. Make the substitutions: u = x/a, v = y/b
Now your ellipse becomes the unit circle, as follows:
b^2*x^2 + a^2*y^2 = a^2*b^2
Divide by a^2*b^2: (x/a)^2 + (y/b)^2 = 1
Substitute u and v: u^2 + v^2 = 1
Now find the equation of tangent line to the unit circle. A line with slope -m (all slopes are negative so m is positive) is tangent to the unit circle where the circle radius has a slope of 1/m. The coordinates of the point on the circle are determined by the two equations:
v/u = 1/m and u^2 + v^2 = 1
Combining: u^2 + (u/m)^2 = 1
Solving: u = sqrt(1/(1 + 1/m^2)) = sqrt(m^2/(m^2 + 1))
Solving for v:
since v^2 = 1 - u^2
v^2 = 1- m^2/(m^2 + 1) = 1/(m^2 + 1)
v = sqrt(1/(m^2 + 1))
Now you have an uv point on the tangent line and the slope (-m)
Using the point slope relation, all that remains is to find the intercept.
v = -mu + c
so c = v + mu = sqrt(1/(m^2 + 1)) + m*sqrt(m^2/(m^2 + 1))
This, being the v-intercept is the height of the triangle. The base of the triangle is the u-intercept for: 0 = -mu + c so u= c/m
The triangle height is c and base is c/m so the area is (c^2)/(2m)
Carry this out and after simplifying you get (c^2)/(2m) = (m^2 + 1)/2m
This is the area in scaled coordinates. We scaled x by a and y by b, that means that tha actual triangle is a time wider and b times higher than this one. Since ab is just a constant multiplier of the area, the maximum area here (in u,v space) represents a maximum area in xy space. So maximize the area as a function of m:
A = (m^2 + 1)/(2m)
dA/dm = 1 - (m^2 + 1)/(2m^2)
Set it equal to zero and solve for m:
0 = 1 - (m^2 + 1)/(2m^2)
2m^2 = m^2 + 1
m = 1
Since m = 1, c= sqrt(1/(m^2 + 1)) + m*sqrt(m^2/(m^2 + 1)) = 2*sqrt(1/2) = sqrt(2)
The triangle base is c/m so that is sqrt(2) as well so the area (in uv space) is sqrt(2)*sqrt(2)/2 = 1.
In xy space, the triangle is a times wider and b times higher so the minimum area is ab and the triangle dimensikons are multiplied by a nad b to be a*sqrt(2) wide by b*sqrt(2) high, the equation of the line follows directly since you have the two points (a*sqrt(2),0) and (0,b*sqrt(2)).
Again y = nx + d
b *sqrt(2) = n*0 + d so d = b*sqrt(2)
0 = n*a*sqrt(2) + b*sqrt(2) so n = -b/a
Giving a final equation of the line then is: y = (-b/a) * x + b*sqrt(2)
2006-12-03 00:28:19
·
answer #2
·
answered by Pretzels 5
·
1⤊
1⤋
Solve equation of ellipse for y.
b^2*x^2 + a^2*y^2 = a^2*b^2
x^2/a^2 + y^2/b^2 = 1
y = b (1 - x^2/a^2)^(1/2)
y = (b/a) (a^2 - x^2)^(1/2)
Here's a handy substitution that I'll use now and then to clean up the algebra and the differentiation.
Q = (a^2 - x^2)^(1/2)
y = (b/a) Q
Find derivative, the slope of the tangent line.
dy/dx = -(b/a) x (a^2-x^2)^(-1/2)
dy/dx = -(b/a) x/Q
Form equation of tangent line.
Y = (dy/dx) X + Y0
Find y intercept of tangent line, in terms of x.
Y0 = Y - (dy/dx) X = y - (dy/dx) x
Y0 = (b/a) {(a^2 - x^2)^(1/2) + x^2 (a^2 - x^2)^(-1/2)}
Y0 = (b/a) {Q + x^2/Q}
Find x intercept, or root, of tangent line, in terms of x.
0 = (dy/dx) X0 + Y0
X0 = -Y0/(dy/dx)
X0 = -(b/a) {Q + x^2/Q} / {-(b/a) x/Q}
x0 = (1/x){Q^2 + x^2}
X0 = (1/x){a^2 - x^2 + x^2}
X0 = a^2/x
Form equation of the area of the triangle bounded by the tangent line and the coordinate axes, and solve for the area in terms of x.
A = (1/2) X0 Y0
A = (1/2) (a^2/x) (b/a) {(a^2 - x^2)^(1/2) + x^2 (a^2 - x^2)^(-1/2)}
A = (ab/2) (1/x) {(a^2 - x^2)^(1/2) + x^2 (a^2 - x^2)^(-1/2)}
A = (ab/2) {Q/x + x/Q}
Find the derivative of the triangle area with respect to the x coordinate of the tangent point.
dA/dx = (ab/2) (-1/x^2) {(a^2 - x^2)^(1/2) + x^2 (a^2 - x^2)^(-1/2)}
+ (ab/2) (1/x) { (1/2)(-2x)(a^2-x^2)^(-1/2) + 2x(a^2-x^2)^(-1/2) + x^2(-1/2)(-2x)(a^2-x^2)^(-3/2)}
dA/dx = - (ab/2) {(1/x^2)(a^2 - x^2)^(1/2) + (a^2 - x^2)^(-1/2)}
+ (ab/2) { (a^2-x^2)^(-1/2) + x^2(a^2-x^2)^(-3/2)}
dA/dx = (ab/2) {-(Q/x^2) - 1/Q + 1/Q + x^2/Q^3}
Find the triangle having minimum area by setting dA/dx=0 and solving for the coordinates of the tangent point [x,y] in terms of (a) and (b).
dA/dx = (ab/2) {x^2/Q^3 - Q/x^2} = 0
x^2/Q^3 = Q/x^2
Q = x = (a^2 - x^2)^(1/2)
x^2 = a^2 - x^2
2 x^2 = a^2
x^2 = a^2/2
x = a / sqrt(2)
y = (b/a) x
y = b / sqrt(2)
The y intercept of the tangent line is
Y0 = (b/a) {Q + x^2/Q}
Y0 = (b/a) 2x
Y0 = (b/a) 2a / sqrt(2)
Y0 = b sqrt(2)
The slope of the tangent line is
dy/dx = -(b/a) x/Q
dy/dx = -(b/a)
The equation of the tangent line is
Y = -(b/a) X + b sqrt(2)
The root of the tangent line is
X0 = a^2/x
X0 = a^2 / [a / sqrt(2)]
X0 = a sqrt(2)
The area of the triangle,
A = (ab/2) {Q/x + x/Q}
A = ab
Area of ellipse = pi a b
Ratio of ellipse area to triangle area = pi
Fraction of the triangle area that is outside the ellipse = 1 - pi/4
2006-12-02 22:43:01
·
answer #3
·
answered by Anonymous
·
0⤊
2⤋
No College
start working earning money=no college debt=more job benefits=employer paying for college classes if you want=more money=success.
2006-12-02 22:09:06
·
answer #4
·
answered by j b 1
·
0⤊
4⤋
find the derivitive!
use the power rule and the chian rule and the multiplication rule all at once on each side, and simplify!
Done.
2006-12-02 21:37:29
·
answer #5
·
answered by Anonymous
·
0⤊
4⤋